GLOBALIZATION OF THE ENGLISH LANGUAGE IN THE MODERN EDUCATIONAL SPACE - Murtazayeva , SH.K. (Educational Research in Universal Sciences, 2023)
The article examines the main characteristics and role of the globalization process in the modern world, as well as its connection with the English language, which occupies the place of the language of world communication in the XXI century.